The role of nickel contact allergy in nummular dermatitis in Indonesia - Niken Indrastuti; Moh Hakimi; Marsetyawan HNE Soesatyo; Hardyanto Soebono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
In the recurrence of nummular dermatitis (ND) as a problem for patients, it is necessary to identify interferon-γ (IFN- γ), interleukin-4 (IL-4), interleukin-17 (IL-17), and stimulation of lymphocytes against nickel. This study aimed to investigate the role of nickel contact allergy in ND. Forty-two patients with ND were studied and 42 healthy subjects who were equal in age, sex and atopy history as control. All subjects underwent nickel skin patch test, detection of IFN-γ, IL-4, IL-17 in blood, and lymphocyte stimulation assays. To determine cut off point of the variables, receiver operator characteristic (ROC) curves were calculated. Bivariate and multivariate analyses were performed to measure the strength of association using odds ratio (ORs) and 95% confidence intervals (95% CI). Statistical analysis was performed using McNemar X2-square test and multiple conditional logistic regression. Nickel contact allergy was shown by nickel patch test (OR= 3.5; 95% CI = 1.09–14.60), stimulation index/SI (OR= 29; 95% CI = 4.81-1184.43), IFN-γ (OR= 4.25; 95% CI = 1.39–17.36). These results were supported after multivariate analysis with conditional logistic regression which showed nickel patch test (OR= 9.63; 95% CI= 1.02–109.38; p= 0.04), SI (OR= 42.19; 95% CI = 2.32–766.03; p= 0.01), IFN-γ (OR= 11.51; 95% CI = 1.08–122.63; p= 0.04). Nickel contact allergy is an important risk factor for ND. Patients with ND are recommended to be tested for nickel contact allergy.